One Malaysia (1 Malaysia) concept and citizen integration through community/neighborhood networking / Rugayah Hj. Hashim...[et al] - Hj. Hashim, Rugayah (Research Management Institute (RMI), 2011)
The objective of this research is to determine the challenges for setting up a community network in a suburban residential area of Selangor, Malaysia. The availability of a community network will allow residents to communicate with one another and inherently will bring them closer and integrate the community. An initial investigation revealed that 12.8% of the residents communicated with one another electronically through mobile phones but not through the proper ICT platform for community networking using the internet. Although the Pearson correlation analysis was positive, the r-value indicated a weak relationship between community networking and citizen integration (r=129, p=.456). Other challenges of implementing a community networking include low levels of education, income and ICT skill. It is suggested that the member of parliament, the state legislative assemblyman, and the Klang Municipal Council work together to promote the awareness of using ICT among the residents as the Federal and State governments' plans for e-government services and achieving the developed nation status by 2020 will not materialize if these suburbanites are marginalized. Also, with the Prime Minister's favored 1 Malaysia concept on citizen integration, this project will also fail in there is limited political will. Integrating the three major races of Malaysia is possible through information and communication technology (ICT) as the enabler.